Sistem Penunjang Keputusan Kelayakan Pendonor Darah Menggunakan Metode SAW di UTD PMI Kota Bengkulu - Moh Syahrul A’dlom; Khairil Khairil; Achmad Fikri Sallaby (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to design a Decision Support System for Blood Donation Eligibility Using the SAW Method at UTD PMI Bengkulu City. Based on the research, UTD PMI Bengkulu City still uses manual calculations in its data processing and does not use a special application. The calculation system still uses Microsoft Word and Microsoft Excel applications which are still less effective and fast. In this research, the method used is SAW (Simple Additive Weighting). This method requires the decision maker to determine the weight of each attribute. The total score for creating an alternative is obtained by adding up all the results of the multiplication between ratings (which can be compared across attributes). The rating for each attribute must be dimension-free in the sense that it has gone through a previous normalization process. In this method, an analysis of the data requirements needed to build the system is carried out, a design plan for the system to be created, compiling and implementing the data that has been obtained into the system. In the new system designed on this occasion several designs were created consisting of designing the File Menu, Data Menu, Process Menu and Report Menu. The programming language used is PHP with a MySQL database.